Sovereign Cocos - Hatchondo, Juan Carlos (IMF Working Papers; Working Paper ;, 2022)
We study a model of equilibrium sovereign default in which the government issues cocos (contingent convertible bonds) that stipulate a suspension of debt payments when the government faces liquidity shocks in the form of an increase of the bondholders' risk aversion. We find that in spite of reducing the frequency of defaults triggered by liquidity shocks, introducing cocos increases the overall default frequency. By mitigating concerns about liquidity, cocos make indebtedness and default risk more attractive for the government. In contrast, cocos that stipulate debt forgiveness when the government faces the shock, achieve larger welfare gains by reducing default risk.